Antiinflammatory and Analgesic Activity of Caesalpinia pulcherrima Linn. Leaf Extracts - Puratchikody, A.; Nagalakshmi, G. (Asian Journal of Chemistry, 2016)
The dried leaves of Caesalpinia pulcherrima are known to possess antiinflammatory and analgesic properties. The present work was carried out to confirm and validate the same, using ethyl acetate and ethanol as solvents in succession and the two different extracts obtained were subjected for screening on albino rats for analgesic and antiinflammatory activity. The results were also compared with pentazocine and diclofenac sodium tablets respectively. The ethyl acetate extract showed better analgesic and antiinflammatory activities compared with ethanolic extract.